Magnetic properties of thermal plasma synthesized nanocrystalline nickel ferrite (NiFe2O4) - Nawale, Ashok B.; Kanhe, Nilesh S.; Patil, K. R.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Journal of Alloys and Compounds, 2011)
A rapid synthesis method is reported for magnetic nanoparticles of nickel ferrite involving thermal plasma assisted vapor phase condensation process. The as-synthesized samples were characterized by X-ray Diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and X-ray Photoelectron Spectroscopy techniques. The average particle size was determined from the TEM micrographs and found to be around 30 nm. The effects of reactor parameters on the magnetic and structural properties have been evaluated, to find the optimized parameters so as to achieve the highest values of saturation magnetization and coercivity. Reasonably high saturation magnetization (48 emu/g) has been assigned to the high degree of crystallinity, achieved on account of high temperature during the growth, and the cation redistribution. The high value of coercivity (1150e) is explained on the basis of possible lattice defects arising from the cation redistribution. Detailed analysis of cation distribution using the XRD line intensity data leads to the conclusion that these samples are iron deficit and nickel rich. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic measurements; Magnetization; Nanostructured materials; TEM

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures

Understanding the growth of micro and nano-crystalline AlN by thermal plasma process - Kanhe, Nilesh S.; Nawale, Ashok B.; Gawade, Rupesh L.; Puranik, Vedavati G.; Bhoraskar, S. V.; Das, Asoka K.; Mathe, Vikas L. (Journal of Crystal Growth, 2012)
We report the studies related to the growth of crystalline AlN in a DC thermal plasma reactor, operated by a transferred arc plasma torch. The reactor is capable of producing the nanoparticles of Al and AlN depending on the composition of the reacting gas. Al and AlN micro crystals are formed at the anode placed on the graphite and nano crystalline Al and AlN gets deposited on the inner surface of the plasma reactor. X-ray diffraction, Raman spectroscopy analysis, single crystal X-ray diffraction and TGA-DTA techniques are used to infer the purity of post process crystals as a hexagonal AlN. The average particle size using SEM was found to be around 30 mu m. The morphology of nanoparticles of Al and AlN, nucleated by gas phase condensation in a homogeneous medium were studied by transmission electron microscopy analysis. The particle ranged in size between 15 and 80 nm in diameter. The possible growth mechanism of crystalline AlN at the anode has been explained on the basis of non-equilibrium processes in the core of the plasma and steep temperature gradient near its periphery. The gas phase species of AlN and various constituent were computed using Murphy code based on minimization of free energy. The process provides 50% yield of microcrystalline AlN and remaining of Al at anode and that of nanocrystalline h-AlN and c-Al collected from the walls of the chamber is about 33% and 67%, respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Crystal morphology; Growth from high temperature solutions; Nitride; Semiconducting aluminum compound

Micro-structural analysis of NiFe2O4 nanoparticles synthesized by thermal plasma route and its suitability for BSA adsorption - Bhosale, Shivaji V.; Kanhe, Nilesh S.; Bhoraskar, S. V.; Bhat, Suresh K.; Bulakhe, Ravindra N.; Shim, Jae-Jin; Mathe, Vikas L. (Journal of Materials Science-Materials in Medicine, 2015)
The paper presents the experimental studies pertaining to the adsorption of bovine serum albumin (BSA) on the nanoparticles of nickel ferrite (NiFe2O4) with a view of correlating the adsorption properties to their microstructure and zeta potentials. Physical properties of two kinds of nickel ferrites, one synthesized by thermal plasma route and the other by chemical co-precipitation method, are compared. Maximum adsorption (231.57 lg/mg) of BSA onto nickel ferrite nanoparticles, at body temperature (37 degrees C) was observed at pH-value of 5.58 for the thermal plasma synthesized particles showing its higher adsorption capacity than those synthesized by wet chemical means (178.71 mu g/mg). Under the same physical conditions the value of zeta potential, obtained for the former, was higher than that of the latter over a wide range of pH values (3.64-9.66). This is attributed to the differences in the specific surface energies of the two kinds of nanoparticles arising from the degree of crystallinity. The paper presents the experimental evidence for the single crystalline nature of the individual nanoparticles, with mean size of 32 nm, for the thermal plasma synthesized particles as evidenced from the high resolution transmission electron microscopy and electron diffraction analysis. The measurements also reveal the poor crystalline morphology in the chemically prepared particles (mean size of 28 nm) although the X-ray diffraction patterns are not much different. The atomic force microscopy images confirm that the surfaces of plasma synthesized nanoparticles possesses higher surface roughness than that of chemically synthesized one. Presence of adsorbed protein was confirmed by vibrational spectroscopy. The Langmuir adsorption model is found to fit into the experimental data better than the Freundlich adsorption model.

Single step, phase controlled, large scale synthesis of ferrimagnetic iron oxide polymorph nanoparticles by thermal plasma route and their rheological properties - Raut, Suyog A.; Mutadak, Pallavi R.; Kumar, Shiv; Kanhe, Nilesh S.; Huprikar, Sameer; Pol, Harshawardhan V.; Phase, Deodatta M.; Bhoraskar, Sudha V.; Mathe, Vikas L. (Journal of Magnetism and Magnetic Materials, 2018)
In this paper we report single step large scale synthesis of highly crystalline iron oxide nanoparticles viz. magnetite (Fe3O4) and maghemite (gamma-Fe2O3) via gas phase condensation process, where micron sized iron metal powder was used as a precursor. Selective phases of iron oxide were obtained by variation of gas flow rate of oxygen and hence partial pressure of oxygen inside the plasma reactor. Most of the particles were found to possesses average crystallite size of about 20-30 nm. The DC magnetization curves recorded indicate almost super-paramagnetic nature of the iron oxide magnetic nanoparticles. Further, iron oxide nanoparticles were analyzed using Raman spectroscopy, X-ray photoelectron spectroscopy and Mossbauer spectroscopy. In order to explore the feasibility of these nanoparticles for magnetic damper application, rheological studies have been carried out and compared with commercially available Carbonyl Iron (CI) particles. The nanoparticles obtained by thermal plasma route show improved dispersion which is useful for rheological applications. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; magnetic properties; Nano-crystalline materials; Rheological properties; Thermal plasma